Factors of human capital development influencing employees' performance in the banking industry of China - Liu, Hai Tao (2007)
The objective of this study is to explain the relationship between Human Capital Development and employees' performance in the banking industry of China. HCD factors consist of training, career development, organization development and management development. Demographic factors consist of age and education level. The sample of this study comprises of the employees of the banking industry of China. For the purpose of this study, the instrument was modified from TV Rao (2005), and the Dimensions of the Learning Organization Questionnaire (OLOQ) developed by Watkins and Marsick (1996, 2003) etc. There are six hypotheses being developed. It's found that training and career development have Significant relationship to the employees' performance in the banking industry of China and these two hypotheses were substantiated. Therefore, this study hoping these results and findings can create awareness and identification to help the employees of China's banking industry to improve their performance in their workplace.